Paternalistic Leadership and Job Embeddedness With Relation to Innovative Work Behaviors and Employee Job Performance: The Moderating Effect of Environmental Dynamism - Yamin, Mohammad Ali (Frontiers in Psychology, 2022)
The current study strives to examine the determinants of employee innovative work behavior and job performance. Therefore, an integrated research model is developed with the help of paternalistic leadership style and job embeddedness theory to investigate employee behavior towards innovative work behavior. The research model is extended with moderating effect of environmental dynamism between the relationship of innovative work behavior and employee job performance. Data were collected from 411 employees working in Small medium enterprises. For inferential analysis, structural equation modeling (SEM) technique is used. Results of the structural equation modeling revealed that altogether paternalistic leadership style and factors underpinned job embeddedness theory have explained 52.1% variance in employees innovate work behaviour. The findings of this research suggest that managers and policy makers should focus on benevolent leadership, moral leadership, and on-the job embeddedness to boost employee job performance and innovative work behavior.